KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPLANASI DENGAN KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 2 BATUSANGKAR - Putri, Sri Rani; Gani, Erizal; Hafrison, Mohammad (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study is three. First, describe the reading skills of explanatory text understanding of class VIII Batusangkar 2 Middle School. Second, describe the explanatory text writing skills of class VIII Batusangkar 2 Middle School. Third, describing reading correlation understanding explanatory text with explanatory text writing skills of class VIII Batusangkar 2 Middle School. This article was written to describe reading skills in understanding explanatory texts with explanatory text writing skills of class VIII students of SMP N 2 Batusangkar. This type of research is quantitative research using descriptive methods. The research design used is correlational. The population in this study was the eighth grade students of SMPN 2 Batusangkar who were enrolled in the 2017/2018 academic year totaling 245 students. Samples were taken using proportional random sampling. Based on the results of this study, it can be concluded that the correlation between reading skills comprehension of explanatory texts and explanatory text writing skills of class VIII Batusangkar 2 Junior High School with 95% evidence with n-1 degrees of freedom; t-count> t-table (5.55)> (1.68). Therefore, reading skills understanding explanatory texts correlate with explanatory text writing skills. Kata Kunci: Korelasi, Keterampilan Membaca Pemahaman Teks Eksplanasi, Keterampilan Menulis Teks Eksplanasi